Implementasi TPACK untuk Meningkatkan Hasil Belajar Peserta Didik XI PS-2 SMKN 2 Malang - Permatasari, Novita; Andarwati, Andarwati; Yulianingsih, Wiwin (Juwara: Jurnal Wawasan dan Aksara, 2024)
This study aims to understand the increase in students' knowledge by applying the TPACK learning approach to class XI students. In accordance with the results of observations that have been carried out previously, there is a tendency that students in class XI PS-2 SMK Negeri 2 Malang have a fairly poor level of understanding of public speaking skills. This is exacerbated by the lack of effective learning approaches used by teachers during the learning process. This research was carried out through the Classroom Action Research (PTK) method which was implemented in two cycles and used research subjects, namely all students of class XI PS-2 SMK Negeri 2 Malang with a total of 29 students consisting of 4 men and 25 women. Based on this research, it can be concluded that there is an increase in knowledge of public speaking skills in XI PS-2 students, this is evidenced by the initial average learning outcomes showed a sufficient understanding category which was originally 81.76 in cycle I there was an increase in the category to very good understanding with an average value of 90.30.